Genomic instabilities in tissue culture : a physiological normality? - Arnholdt-Schmitt, Birgit; Justus Liebig University Giessen (My University, 2001)
In the present paper, the general role of in vitro culture systems for fundamental research in plant sciences is stressed. As an example, studies on the effect of physiological stimuli on genome variation are presented. The results of systematic investigations on 37 primary callus culture variants derived from secondary phloem of carrot roots indicated a drasticdiminution in repetitive DNA fractions as a predominant change at the total genome level during high cell division growth. Also, RAPD fingerprint analyses confirmed reproducible quantitative polymorphism in primary cultures due to the effects of tissue culture and growth regulators. The general implication of these results could be confirmed by in vivo - studies on different tissues and tissues of different ages.
Keywords: ddc:570